Structural Breaks and the Long-Run Stability of Demand for Real Broad Money Function in Nigeria: A Gregory-Hansen Approach - Nduka, Eleanya Kalu (The Economics and Finance Letters, 2014)
This study examines the long-run demand for real broad money function and its stability in Nigeria for the period from 1970 to 2012 inclusive. The study employs the Augmented-Dickey Fuller and Phillips-Perron tests for unit root, the Gregory and Hanson (1996a; 1996b) cointegration test to capture endogenous structural breaks in the cointegrating vectors of Nigerian long-run money demand function, cumulative sum of recursive residuals (CUSUM) and cumulative sum of recursive residuals squares (CUSUMSQ) tests for structural stability proposed by Brown et al. (1975). In estimating the canonical specification models, extended specifications are also presented. The results of the cointegration test suggest that demand for real broad money went through a regime shift in 2005. The results further confirm that there exists a long-run relationship amongst real broad money demand, real income, real domestic interest rate, real exchange rate, rate of inflation and foreign interest rate. However, the result of CUSUMSQ shows that the demand for money function is stable, but has undergone some temporary periods of instability. Hence, the apex bank in Nigeria can target the broad money (M2) aggregate to achieve macroeconomic objectives.